KETIKA MEMBUNUH MENJADI SEBUAH PENYELESAIAN: Sebuah Tinjauan Fenomenologis Mengenai Tindakan Seseorang Melakukan Pembunuhan - Wahyudi, Agus (The Journal of Society and Media, 2018)
Murder  is  an  evil  action  to  take  the  soul  of  others.  Everyone  can  be  a murderer. Socio-culture background (age, sex, socio-enonomic, ethnic, religion) is not the reason or someone to kill others. Many factors make someone decide to kill others. One of the factors is known as killing  motive. This qualitative  research used the primary data. Subject were 5 people. There were 4 motives to kill, they are polygamy, money, loan, and frustration motive.